Social Media Marketing on Purchase Intention through Mediated Variables of Perceived Value and Perceived Risk - Chafidon, Muhammad Asep Awaludin Zainal; Margono, Margono; Sunaryo, Sunaryo (International Journal Labs, 2022)
During the COVID-19 pandemic, there was an increase in e-commerce transactions. In 2020, there was an increase in the nominal e-commerce transactions by 29.6% from IDR 205.5 trillion in 2019 to IDR 266.3 trillion. This increase in sales from e-commerce makes manufacturers one of the opportunities to increase sales of their products by utilizing the internet network to make it easier to communicate and market their products. The research discusses how social media marketing affects purchase intention through mediated variables, namely perceived value and perceived risk. This research used the quantitative approach with explanatory research. This research was conducted offline through the distribution of questionnaires and online through online questionnaires given to market place consumers who have the desire to make purchases in cash on delivery on e-commerce without a purchase platform. This research was conducted on e-commerce consumers in Malang. Social media marketing in this study has a positive influence on purchase intention, perceived value, and perceive risk. Social media marketing in this study has been shown to affect purchase intentions that are mediated by perceived value. On the other hand, it does not affect purchase intentions that are mediated with perceived risk.